Randomized Controlled Trial of Low-Dose Aspirin in Reducing Pregnancy Loss in Women with Antiphospholipid Syndrome - Neena jamil, Rashida Kousar,Fareeha Faryal. Aneeza Sikander,Wajiha, Sania Ali, Farah Naz Tahir, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Antiphospholipid syndrome (APS) is a significant contributor to recurrent pregnancy loss (RPL), primarily due to its prothrombotic effects. This randomized controlled trial aimed to evaluate the efficacy of low-dose aspirin